Pengaruh Profitabilitas, Ukuran Perusahaan dan Capital Intensity Terhadap Agresivitas Pajak di Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Marhan, Fahrul; Hasanah, Nuramalia; Utaminingtyas, Tri Hesti (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of profitability, company size, and capital intensity on tax aggressiveness. This study used a sample of property and real estate companies listed on the Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling. This study of the research analysis uses the SPSS 2.5 for windows application. Tax aggressiveness as an independent variable is proxied by effective tax rate (ETR). While the dependent variable in this study is profitability proxied by Return On Asset (ROA), the company size variable is proxied by the natural Log of total assets, and the capital intensity variable is proxied by total net fixed assets divided by total assets. The results obtained in the following study, profitability and capital intensity have accepted and have an effect on tax aggressiveness while company size has no influence on tax aggressiveness.